Comprehensive Analysis of Formation Water Microorganisms for Their Biosurfactant Potential in MEOR Applications - Gulzhan Kaiyrmanova; Ulzhan Shaimerdenova; Alisher Assylbek; Almira Amirgaliyeva; Arailym Yerzhan; Aliya Yernazarova (Fermentation)
The study is devoted to the analysis of the physicochemical parameters of formation waters, the metagenomic composition of the microbial community and the characteristics of bacterial isolates from the oil fields of Western Kazakhstan to assess their potential in microbial-enhanced oil recovery (MEOR) technologies. Analyses revealed an adaptation of local microorganisms to extreme conditions of high salinity, temperature and pressure, with the dominant presence of Proteobacteria, including the genus Marinobacter. Screening isolates for biosurfactant synthesis showed a high activity of strains M22-7, M93-8C and M142-2, capable of reducing surface tension to 28.81 ± 0.6 mN/m and forming emulsions. Genetic analysis confirmed the presence of key genes (srfAA, srfp) responsible for surfactin synthesis, but the absence of lchAA and rhlAA indicates that the synthesis of other types of biosurfactants is limited. The results highlight the promise of developing microbial consortia and using biosurfactants in high-salinity environments to enhance oil recovery.